Greek Buddha : Pyrrho's encounter with early Buddhism in Central Asia - Beckwith, Christopher I., 1945- (Princeton University Press, 2015)
Pyrrho of Elis accompanied Alexander the Great to Central Asia and India during the Graeco-Macedonian invasion and conquest of the Persian Empire in 334-324 BC, and while there met with teachers of Early Buddhism. Greek Buddha shows how Buddhism shaped the philosophy of Pyrrho, the famous founder of Pyrrhonian scepticism in ancient Greece. Identifying Pyrrho's basic teachings with those of Early Buddhism, Christopher I. Beckwith traces the origins of a major tradition in Greek philosophy to Gandhāra, a country in Central Asia and northwestern India. Using a range of primary sources, he syste.